Trauma‐induced hypocalcemia. (24th June 2022) - DeBot, Margot; Sauaia, Angela; Schaid, Terry; Moore, Ernest E.
Abstract: Background: Trauma‐induced hypocalcemia is an underappreciated complication of severe injury but is well known to result in the derangement of an array of physiological regulatory mechanisms. Existing literature provides a compelling link between hypocalcemia and worse trauma‐induced coagulopathy and increased mortality after injury. Study Design and Methods: This narrative review evaluates available data related to the risk factors, mechanisms, and treatment of hypocalcemia after severe injury. The authors did not perform a systemic review or meta‐analysis. Results and Discussion: The interplay of acidosis, hypothermia, and coagulopathy with hypocalcemia potentiates the bloody vicious cycle of hemorrhagic shock which has been the paradigm of trauma resuscitation for over half a century. However, current screening and treatment of postinjury hypocalcemia are relegated to a secondary consideration in trauma resuscitation. We conclude calcium supplementation should be a primary tier intervention for life‐threatening injury.